Hubungan Keragaman Pangan Individu dan Status Gizi Anak 2-5 Tahun di Desa Batur Kecamatan Getasan Kabupaten Semarang: Correlation between Individual Dietary Diversity and Children 2-5 Years Old Nutrition Status in Batur Village, Getasan Regency, Semarang District - Age Prasetyo; Sarah Melati Davidson; Theresia Pratiwi Elingsetyo Sanubari (Amerta Nutrition, 2023)
Background: In the rural area, food security problem tends to be a challenge. This situation arose because of the lack of dietary diversity and impacted family nutrition, especially for infants. Objectives: This study aimed to determine the correlation between individual food diversity and the nutritional status of children 2-5 years in Batur Village, Semarang District, Indonesia. Methods: Observational research with a cross-sectional design was carried out. The respondents were families with toddlers aged 2-5 years and members of the Integrated Service Post (Posyandu) in Batur Village, Getasan Health Center. This research instrument used a food recall questionnaire 1x24-h and was processed based on the Individual Dietary Diversity Score (IDDS). Sampling was done by simple random sampling technique for 95 toddlers. Results: There was a significant correlation between food diversity and children's nutritional status under five. The HAZ correlation value is r=0.618; p<0.001. The WAZ correlation value is r=0.545; p<0.001; the WHZ correlation value is r=0.325; p=0.001. A significant correlation was found between the variety of foods in the IDDS and the nutritional status of the HAZ (r=0.618). Conclusions: Food diversity is one of the factors associated with the occurrence of nutritional problems for infants in Batur Village.